Considering social determinants of health in the relationship between physical activity and exercise engagement and cognitive impairment among persons with epilepsy - Hansen, Barbara; Allendorfer, Jane B. (Frontiers in Rehabilitation Sciences, 2022)
Many persons with epilepsy (PWE) are not as active or physically fit as compared to the general population. This lack of engagement in physical activity has been attributed to a number of factors, few of which take into consideration the social determinants of health (SDH). In this perspective, we highlight how SDH are considered in explaining lower levels of physical activity engagement among PWE, particularly for those experiencing cognitive impairment. We also discuss how these data can be applied in research to yield a greater impact on the quality of life among PWE. Consideration of SDH allows for increased understanding of how cognition can be both a determinant of physical activity and an outcome of environments conducive to physical activity in PWE.